2017
DOI: 10.18632/oncotarget.21215
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-101 promotes TRAIL-induced mitochondrial apoptosis in papillary thyroid carcinoma by targeting c-met and MCL-1

Abstract: Tumor necrosis factor-related apoptosis inducing ligand (TRAIL) induces apoptosis in malignant cells, but not in normal cells. As papillary thyroid carcinoma cells broadly expressed TRAIL receptors (death receptor 4 and death receptor 5) on their surface, TRAIL is considered as a promising drug for treatment of papillary thyroid carcinoma. However, resistance to TRAIL still be a big obstacle to achieve a satisfactory effect for cancer therapy. Here, we found that overexpression of miR-101 was able to sensitize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…More importantly, although its role in OA has rarely been reported, miR-101 is well-known for its tumor suppressive function. By promoting cancer cell apoptosis, miR-101 can serve as a tumor suppressor [47][48][49]. In nasopharyngeal carcinoma cells, miR-101 exerted its apoptosis-promoting function by inhibiting the Ras/Raf/MEK/ERK signaling pathway [47].…”
Section: Agingmentioning
confidence: 99%
“…More importantly, although its role in OA has rarely been reported, miR-101 is well-known for its tumor suppressive function. By promoting cancer cell apoptosis, miR-101 can serve as a tumor suppressor [47][48][49]. In nasopharyngeal carcinoma cells, miR-101 exerted its apoptosis-promoting function by inhibiting the Ras/Raf/MEK/ERK signaling pathway [47].…”
Section: Agingmentioning
confidence: 99%
“…Although many achievements have been made in thyroid carcinoma treatment, the survival, and existence of patients remain unsatisfactory (3). Because of the few clinical indications, most patients are diagnosed only in the late stage and have little probability to obtain efficient and helpful treatment (4). Therefore, the exploration of new cancer-specific biomarkers will lead to clinical therapy and improve the patient diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al 19 reported that miR-101 reduces PTC cell proliferation, apoptosis resistance, migration, and invasion in vitro and suppresses tumor growth and metastasis in vivo by targeting USP22. miR-101 was able to sensitize PTC cells to TRAIL treatment in vitro and in vivo through driving TRAIL-induced mitochondrial apoptosis by targeting c-met and MCL-1 20 . Consistently, in this study, we demonstrated that miR-101 was pronouncedly downregulated in PTC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, miRNA-101 (miR-101) affords tumor-suppressive roles in a variety of human malignancies, such as breast cancer 12 , colon cancer 13 , lung cancer 14 , hepatocellular carcinoma 15 , gastric cancer 16 , and PTC 17–20 . Reportedly, miR-101 inhibits PTC cell proliferation, migration, and invasion by targeting Rac1 17,18 , hinders tumorigenesis of PTC in vitro and in vivo by downregulating USP22 19 , and promotes TRAIL-induced mitochondrial apoptosis of PTC cells by targeting c-met and Mcl-1 20 . However, knowledge is limited on the mechanisms by which miR-101 reduces the vicious behaviors of PTC.…”
Section: Introductionmentioning
confidence: 99%